Retracted: What do women in rural Bareilly think about postmenopausal bleeding? A mixed-method study - Agarwal, Medhavi; Upadhayay, Deepak; Katyal, Rashmi (International Journal Of Community Medicine And Public Health, 2021)
The article "What do women in rural Bareilly think about postmenopausal bleeding? A mixed-method study" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Community Medicine and Public Health. The article is retracted when found similar with an article published by Dr. Sindhuri R. (Indian J Community Med 2021;46:145-8; DOI: https://dx.doi.org/10.4103/ijcm.IJCM_446_20), which violates publication ethics and academic practice.